Functional Brain Network Changes Following Use of an Allostatic, Closed‐Loop, Acoustic Stimulation Neurotechnology for Military‐Related Traumatic Stress. Issue 1 (10th October 2018) - Lee, Sung W.; Laurienti, Paul J.; Burdette, Jonathan H.; Tegeler, Catherine L.; Morgan, Ashley R.; Simpson, Sean L.; Gerdes, Lee; Tegeler, Charles H.
ABSTRACT: BACKGROUND AND PURPOSE: Post‐traumatic stress disorder is associated with connectivity changes in the default mode, central executive, and salience networks, and other brain regions. This study evaluated changes in network connectivity associated with usage of High‐resolution, relational, resonance‐based electroencephalic mirroring (HIRREM ® ; Brain State Technologies, Scottsdale, AZ), a closed‐loop, allostatic, acoustic stimulation neurotechnology, for military‐related traumatic stress. METHODS: Eighteen participants (17 males, mean age 41 years [SD = 7], 15 active duty) enrolled in an IRB approved pilot trial for symptoms of military‐related traumatic stress. Participants received 19.5 (1.1) HIRREM sessions over 12 days. Symptoms, physiological and functional measures, and whole brain resting MRI were collected before and after HIRREM. Six whole brain functional networks were evaluated using summary variables and community structure of predefined networks. Pre to postintervention change was analyzed using paired‐sample statistical tests. RESULTS: Postintervention, there was an overall increase in connectivity of the default mode network ( P = .0094). There were decreases of community structure in both the anterior portion of the default mode (medial prefrontal cortex, P = .0097) and in the sensorimotor ( P = .005) network. There were no statistically significant changes at the whole brain level, or in the central executive, salience, or other networks analyzed. Participants demonstrated significant improvements in clinical symptoms, as well as autonomic cardiovascular regulation, which have been reported previously. CONCLUSIONS: Use of closed‐loop, allostatic, acoustic stimulation neurotechnology (HIRREM) was associated with connectivity changes in the default mode and sensorimotor networks, in directions that may have explained the subjects' clinical improvements.